Recognition of the First Language and Second Language Learning from the Perspective of the Holistic Approach to the Inclusion of Immigrant Children in Slovenian Kindergartens and Schools - Rutar, Sonja; Pevec Semec, Katica (Revija za elementarno izobraževanje, 2024)
The paper presents the results of a qualitative study that explored the practices of identifying the language needs of immigrant children; the importance practitioners attach to an integrated approach to the inclusion of immigrant children at different levels; and the challenges they expect to face in implementing the concept of an integrated approach with parents, head teachers, teaching and non-teaching staff. The study involved 209 professionals from kindergartens, primary and secondary schools who received training on the implementation of the Concept for the Holistic Integration of Immigrant Children in Kindergartens and Schools. The results show that kindergartens and schools recognise the linguistic needs of immigrant children, stress the importance of preserving the first language as a contribution to understanding different cultures, developing identity and encouraging the learning of a second or foreign language.
Keywords: parents, teachers, educators, inclusion, quality.